Gain Study of an Edge Emitting Laser for Optical Fiber Communication System - Faten Adel Ismael Chaqmaqchee (Journal of Basic & Applied Sciences, 2016)
In this work, an optical gain around 1 dB of an edge emitting laser (EEL) has been obtained applying threshold current of 22 mA. The conventional device lased at around 1.3 µm with 0.3 nm stripe width at room temperature. The device was also characterised through output light-voltage-current using current-temperature (I-T) controllers and optical spectrum analyser (OSA). ConventionalEEL isactually a form of semiconductor lasers that propagates the light in a direction along the wafer surface of laser chip and their emitted light is reflected at a cleaved edge. The cleaved facets of the device acts as mirrors, reflecting photons back into the resonator and the stimulated emission occurs within cavity region forgain achievement..